Electromagnetic Navigational Bronchoscopy Reduces the Time Required for Localization and Resection of Lung Nodules. Issue 5 (September 2017) - Bolton, William David; Cochran, Thomas; Ben-Or, Sharon; Stephenson, James E.; Ellis, William; Hale, Allyson L.; Binks, Andrew P.
Abstract : Objective: The aims of the study were to evaluate electromagnetic navigational bronchoscopy (ENB) and computed tomography–guided placement as localization techniques for minimally invasive resection of small pulmonary nodules and determine whether electromagnetic navigational bronchoscopy is a safer and more effective method than computed tomography–guided localization. Methods: We performed a retrospective review of our thoracic surgery database to identify patients who underwent minimally invasive resection for a pulmonary mass and used either electromagnetic navigational bronchoscopy or computed tomography–guided localization techniques between July 2011 and May 2015. Results: Three hundred eighty-three patients had a minimally invasive resection during our study period, 117 of whom underwent electromagnetic navigational bronchoscopy or computed tomography localization (electromagnetic navigational bronchoscopy = 81; computed tomography = 36). There was no significant difference between computed tomography and electromagnetic navigational bronchoscopy patient groups with regard to age, sex, race, pathology, nodule size, or location. Both computed tomography and electromagnetic navigational bronchoscopy were 100% successful at localizing the mass, and there was no difference in the type of definitive surgical resection (wedge, segmentectomy, or lobectomy) ( P = 0.320). Postoperative complications occurred in 36% of all patients, but there were no complications related to the localization procedures. In terms of localization time and surgical time, there was no difference between groups. However, the down/wait time between localization and resection was significant (computed tomography = 189 minutes; electromagnetic navigational bronchoscopy = 27 minutes); this explains why the difference in total time (sum of localization, down, and surgery) was significant ( P < 0.001). Conclusions: We found electromagnetic navigational bronchoscopy to be as safe and effective as computed tomography–guided wire placement and to provide a significantly decreased down time between localization and surgical resection.